"Inclusión de harina de fréjol de palo /cajanus cajan - I, millsp) en el alimento de pollos de engorde y su efecto en parámetros productivos" - Zambrano Flecher, René Fernando (2014)
ABSTRACT The following research was conducted to evaluate the influence of bean flour stick (Cajanus cajan - L, Millsp) as an alternative protein source for broilers, environmental and economic impact was conducted in Zapallo parish - Flavio Alfaro canton. There were evaluated 4 levels of bean flour stick (T1: 0%; T2: 5%; T3: 10%; T4: 15%); for which 320 broilers of the COBB line 500, 4 replicates per treatment - 20 chicks per replicate. The average weight increased, the T1 obtained (62.5 g), also the best feed conversion was for T1 (1.70 Kg/Kg); the lowest weekly food consumption was awarded to T1 (4,44 Kg). The highest average weight reported by the T1 (2,65 Kg). All the treatments had different behaviors in each of the measured variables (P<0.05) except for the food consumption variable accumulated at day 42 showing no significant difference between treatments, most protein excretion in the stool scored T4 update in day 21 and day 42 (5.01%) and (5.09%), respectively on wet basis. In addition it was determined that in the control group of birds a better profit $0, 83 cents for each dollar invested. We concluded they can be Used by 10% inclusion positive effect in the different production indicators.